Length of Barrett's oesophagus and cancer risk: implications from a large sample of patients with early oesophageal adenocarcinoma. Issue 2 (25th June 2015) - Pohl, Heiko; Pech, Oliver; Arash, Haris; Stolte, Manfred; Manner, Hendrik; May, Andrea; Kraywinkel, Klaus; Sonnenberg, Amnon; Ell, Christian
Abstract : Objective: Although it is well understood that the risk of oesophageal adenocarcinoma increases with Barrett length, transition risks for cancer associated with different Barrett lengths are unknown. We aimed to estimate annual cancer transition rates for patients with long-segment (≥3 cm), short-segment (≥1 to <3 cm) and ultra-short-segment (<1 cm) Barrett's oesophagus. Design: We used three data sources to estimate the annual cancer transition rates for each Barrett length category: (1) the distribution of long, short and ultra-short Barrett's oesophagus among a large German cohort with newly diagnosed T1 oesophageal adenocarcinoma; (2) population-based German incidence of oesophageal adenocarcinoma; and (3) published estimates of the population prevalence of Barrett's oesophagus for each Barrett length category. Results: Among 1017 patients with newly diagnosed T1 oesophageal adenocarcinoma, 573 (56%) had long-segment, 240 (24%) short-segment and 204 (20%) ultra-short-segment Barrett's oesophagus. The base-case estimates for the prevalence of Barrett's oesophagus among the general population were 1.5%, 5% and 14%, respectively. The annual cancer transition rates for patients with long, short and ultra-short Barrett's oesophagus were 0.22%, 0.03% and 0.01%, respectively. To detect one cancer, 450 patients with long-segment Barrett's oesophagus would need to undergo annual surveillance endoscopy; in short segment and ultra-short segment, the corresponding numbers of patients would be 3440 and 12 364. Similar results were obtained when applying US incidence data. Conclusions: The large number of patients, who need to undergo endoscopic surveillance to detect one cancer, raises questions about the value of surveillance endoscopy in patients with short segment or ultra-short segment of Barrett's oesophagus.